If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -15 = -21 Reorder the terms: -15 + 2x = -21 Solving -15 + 2x = -21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 2x = -21 + 15 Combine like terms: -15 + 15 = 0 0 + 2x = -21 + 15 2x = -21 + 15 Combine like terms: -21 + 15 = -6 2x = -6 Divide each side by '2'. x = -3 Simplifying x = -3
| 24x+3y+7x-9y= | | -(y-3x-2)= | | -5*x-7=-7 | | 9p+6=15+8p | | 10x+45=5(2x+9) | | 2(3)-4(5)= | | -5*x-7=-127 | | 7x=1050 | | -5*x-7=-100 | | 2x=3xm+15x-2m-10 | | -5*x-7=100 | | -2(-3v^2+2-3u^3)= | | 5*x-7=100 | | 2x=468 | | s(t)=-16t^2+96t+20 | | -2x+2=-46 | | s(t)=-16t+96t+20 | | x+x+56 = 180 | | 1/2(x+2)=1/3x-6 | | (x-6)(x^2-5x+7)= | | t=16t+96t+20 | | -17=(-5)(2)+x | | 1/2x-1/3x=-5 | | n/7.7=13.7 | | (2-5w+2y)(-8)= | | t=-16t^2+96t+20 | | 17=(-5)(2)+x | | x/2=60 | | 1/2x-1/3x=-4 | | 24x+8=4(6x+2) | | (74x+6y)+(7x-9y)= | | -6(-5x-3u+4)= |